Exploring the impact of pulse oximeter selection within the COVID-19 home-use pulse oximetry pathways. Issue 1 (9th February 2022) - Stell, David; Noble, Jonathan James; Kay, Rebecca Hazell; Kwong, Man Ting; Jeffryes, Michael John Russell; Johnston, Liam; Glover, Guy; Akinluyi, Emmanuel
Abstract : Background: During the COVID-19 pandemic, portable pulse oximeters were issued to some patients to permit home monitoring and alleviate pressure on inpatient wards. Concerns were raised about the accuracy of these devices in some patient groups. This study was conducted in response to these concerns. Objectives: To evaluate the performance characteristics of five portable pulse oximeters and their suitability for deployment on home-use pulse oximetry pathways created during the COVID-19 pandemic. This study considered the effects of different device models and patient characteristics on pulse oximeter accuracy, false negative and false positive rate. Methods: A total of 915 oxygen saturation (sp O2 ) measurements, paired with measurements from a hospital-standard pulse oximeter, were taken from 50 patients recruited from respiratory wards and the intensive care unit at an acute hospital in London. The effects of device model and several patient characteristics on bias, false negative and false positive likelihood were evaluated using multiple regression analyses. Results and conclusions: All five portable pulse oximeters appeared to outperform the standard to which they were manufactured. Device model, patient sp O2 and patient skin colour were significant predictors of measurement bias, false positive and false negative rate, with some variation between models. The false positive and false negative rates were 11.2% and 24.5%, respectively, with substantial variation between models.